Visual Variables in Exterior Advertisements Design Structure: أكرم جرجيس نعمة -عبد الله جاسم غريب (Al-Academy, 2020)
What makes the commercial advertisement distinct is the design structure which is built according to artistic and creative concepts and terms based on the visual and formal interdependence relationships to express the motives of the advertising idea, which is based in its action mechanism on the effective variables, some of which are related to the marketing aspect, and others related to the advertisement aspect. The major aspect is the functional and aesthetic variables, which are represented by the vocabulary of the advertisement area for the open spaces such as the street ads. Its promotional dimension is the active forces in the circulation of commodities and products. Therefore, there would be significant problems the designer rectifies to achieve more attraction, attention, and demand, as he derives that from the design action variables.